Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

[(M^2N^2-MN)(M^2N^2+MN)]/MN

Sagot :

Answer:

Step-by-step explanation:

M²N² - MN = MN (MN - 1)

M²N² + MN = MN (MN + 1)

[tex]\frac{(M^{2}N^{2}-MN)(M^{2}N^{2}-MN)}{MN}= \frac{MN(MN-1) * MN(MN + 1)}{MN}\\[/tex]

                                     = (MN - 1) * MN * (MN + 1)

                                     = (MN - 1)(MN +1) MN             {(a+ b)(a - b) = a² - b² }

                                     = (M²N² - 1²) * MN

                                    = (M²N² - 1)MN